2023
DOI: 10.1186/s12912-023-01544-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a co-designed Parkinson’s awareness audio podcast for undergraduate nursing students in Northern Ireland

Sophie Crooks,
Patrick Stark,
Susan Carlisle
et al.

Abstract: Background Parkinson’s Disease (PD) is a common neurological condition that often causes stiffness, tremor and slow movement. People living with PD are likely to encounter nursing students throughout their journey from pre-diagnosis to death. Despite this, there is a paucity of evidence about current practice in PD education amongst nursing students. The present study provides an evaluation of a co-designed Parkinson’s Awareness audio podcast amongst nursing students in Northern Ireland. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The co-design approach proves invaluable for crafting education resources among student populations, as it actively involves them as end-users. This participatory method empowers students to prioritise and shape the content based on their preferences and specific learning needs, ensuring the resulting resources align closely with their educational requirements and enhance overall engagement [ 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…The co-design approach proves invaluable for crafting education resources among student populations, as it actively involves them as end-users. This participatory method empowers students to prioritise and shape the content based on their preferences and specific learning needs, ensuring the resulting resources align closely with their educational requirements and enhance overall engagement [ 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…The implementation of podcasting in nursing education is one strategy to enhance learning, as discussed in the literature. Recent research conducted in Northern Ireland on podcasting to improve undergraduate nursing students’ awareness of Parkinson Disease found that “podcasting as an educational resource for undergraduate student nurses is a successful way of developing knowledge for PD [Parkinson disease]” [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This number is set to sharply increase in the coming decades [13]. Despite this increasing prevalence of PD globally, and a substantial proportion living within care homes, existing literature has suggested that the care needs of people with PD and their lived experience within care homes remains poorly understood [14,15].…”
Section: Introductionmentioning
confidence: 99%